Pregnancy outcomes in women with preexisting thyroid diseases: a French cohort study. (10th October 2021) - Lecorguillé, Marion; Léger, Juliane; Forhan, Anne; Cheminat, Marie; Dufourg, Marie-Noëlle; Heude, Barbara; Charles, Marie-Aline
Abstract: Women with thyroid diseases at the beginning of pregnancy may have suboptimal thyroid hormone levels because of potential difficulties in compensating for the physiological thyroid hormone changes occurring in pregnancy. Our objective was to study the association between preexisting thyroid diseases, pregnancy complications, and neonatal anthropometry. In total, 16, 395 women from the ELFE French longitudinal birth cohort were included, and 273 declared pre-pregnancy thyroid diseases. Associations were investigated with multivariable regression models, with adjustment for relevant potential confounders. Body mass index (BMI) was additionally adjusted for in a second stage. As compared with other women, women with pre-pregnancy thyroid diseases were more frequently obese (19.6% vs. 9.8%) and had greater odds of gestational diabetes development (odds ratio [OR] = 1.58 [95% confidence interval [CI] 1.08, 2.30]) or had undergone treatment for infertility (OR = 1.57 [95% CI 1.07, 2.31]). After adjustment for BMI, the association with gestational diabetes was no longer significant (OR = 1.27 [95% CI 0.86, 1.88]). After excluding women with another medical history, those with pre-pregnancy thyroid diseases had increased odds of premature rupture of membranes (OR = 1.51 [95% CI 1.01, 2.25]). Children born from mothers with hypothyroidism before conception due to a disease or as a potential side effect of treatment had a smaller head circumference at birth than other children ( β = −0.23 [95% CI −0.44, −0.01] cm). In conclusion, pre-pregnancy thyroid diseases were associated with risk of infertility treatment, gestational diabetes, and premature rupture of membranes. The association between history of hypothyroidism and moderate adverse effects on fetal head circumference growth needs replication.